Pengaruh Word Of Mouth, Kualitas Produk, dan Brand Image Terhadap Keputusan Pembelian Ulang Hand & Body Lotion Mariana di Surabaya - Insanniat, Ulummil; Soebiantoro, Ugy (Jurnal E-Bis, 2022)
One industry that is currently facing intense competition is the body skincare industry. Body care products are daily necessities for men and women, one of which is hand and body lotion products. On the other hand, increasingly stringent economic developments make companies compete with each other. The aim is to determine the effect of Word Of Mouth, Product Quality, and Brand Image on the Decision to Repurchase Marina's Hand & Body Lotion in Surabaya. Data collection was carried out by giving questionnaires on google form to 90 respondents who had purchased Marina Hand and Body Lotion products in Surabaya using the Purposive Sampling technique. The data collected is then managed using Partial Least Square (PLS). The results of this study explain that Word of Mouth, Product Quality and Brand Image have a positive and significant influence on the Decision to Repurchase Hand and Body Lotion Marina in Surabaya.